2008
DOI: 10.2165/00063030-200822040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Autologous T-Cell Vaccination for Multiple Sclerosis

Abstract: T-cell vaccination (TCV) is a unique approach to induce immune regulation that may have importance in the treatment of autoimmune diseases, including multiple sclerosis (MS). TCV employs a classic vaccine strategy of injecting an attenuated form of the disease-causing agent--in this case, myelin-reactive T cells--that have been selected and expanded from each MS donor and then re-injected after irradiation to induce protective immunity. This anti-T-cell immunity consistently results in selective deletion or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…TCR immunogenicity provides the rationale for using T-cell vaccination to induce anti-idiotypic immune responses with the purpose of down-regulating functionality of idiotype-bearing, self-reactive T-cells. The disappearance of T-cell clones used in the vaccination procedure has been one of the most consistent findings of the various studies (Vandenbark & Abulafia-Lapid 2008).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…TCR immunogenicity provides the rationale for using T-cell vaccination to induce anti-idiotypic immune responses with the purpose of down-regulating functionality of idiotype-bearing, self-reactive T-cells. The disappearance of T-cell clones used in the vaccination procedure has been one of the most consistent findings of the various studies (Vandenbark & Abulafia-Lapid 2008).…”
Section: Introductionmentioning
confidence: 54%
“…Of great importance is that the variable TCR regions are finally formed in the post-natal period and, therefore, no innate immune tolerance to them exists in the adult body. Moreover, idiotypic TCR determinants are firmly established to be immunogenic and capable of eliciting an anti-idiotype immune responses, which are implicated in down-regulation of autoimmune processes (Seledtsov et al 2010;Vandenbark & Abulafia-Lapid 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of animal studies and human clinical trials of T-cell vaccination in MS have been conducted and reviewed [166,167]. TCV include an attenuation step to preventing the encephalitogenicity of myelin-reactive T cells and is safe.…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%
“…TCV include an attenuation step to preventing the encephalitogenicity of myelin-reactive T cells and is safe. Two phase II, placebo-controlled clinical trials of TCV in MS were reported [167,168]. Fox et al showed that treatment with myelin-reactive T-cells against up to six peptides of MBP, MOG and PLP was safe in 100 RRMS and CIS patients, of which 44% were previously treated with DMTs [168].…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%